Operations manual. - Philippine Public Safety College ([Makati City] PPSC, 1996)
This PPSC operations manual is a detailed manual about the creation, operation, and planning and research of the Philippine Public Safety College. Gives the whole constitution governing the Philippine Public Safety College.
Cover title.
Keywords: Philippine Public Safety College (Makati City) -- Handbooks, manuals, etc